PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM PERSPEKTIF TEORI BELAJAR HUMANISTIK - Rukmi, Dian Aprelia; Mutiah, Titik (Jurnal Pendidikan Dasar Flobamorata, 2023)
This research aims to find out the application of differentiated learning from the perspective of humanistic learning theory. The concept used in this research provides nearly the same concept between differentiated learning and humanistic learning theory because both of them provide an understanding of the importance of humanizing humans to suit their characteristic. This research was conducted on 5th grade students of SD Negeri Kiyaran 2 Cangkringan. The method of this research used descriptive qualitative with a case study approach. The researcher in this research hope to find natural patterns that occur in the application of differentiated learning in the perspective of humanistic learning theory that occurs in the classroom. The researcher of this research observed learning activities starting from planning, implementing, and evaluating during the implementation of differentiated learning. The researcher gathered the data by used diagnostic tests, observation, work method, and final tests. The subjects of this research were the 5th grade students of SD Negeri Kiyaran 2 Cangkringan in the 2022/2023 academic year with a total of 14 students, consisting of 8 boys and 6 girls. The results of this research showed that the used of differentiated learning in the perspective of learning theory has a positive influence on creativity and learning outcomes of students. This is indicated by the increase in the average value of the creativity on students from the initial condition of 67.86 to 80.21. Moreover, differentiated learning in the perspective of learning theory can improve student learning outcomes by showing the average test score which was initially 79.29 increased to 84,86.